Technology Readiness Among Future Accountants Towards Digitalization of Accounting Profession - Shazalina Mohamed Shuhidan; Yunita Awang; Azuraidah Taib; Norfadzilah Rashid; Mohd Sidki Hasan (Indonesian Journal of Sustainability Accounting and Management, 2023)
As the digital world evolves, accounting professionals must embrace the digital shift to remain relevant. Future accountants must be equipped with the most up-to-date technological knowledge. Thus, this study investigates the link between optimism, innovativeness, discomfort, and insecurity about technology with technology readiness for the digitalization of the accounting profession among future accountants. This study employs a non-probability purposive sampling approach with future accountants as the research unit. Online surveys are used to gather data for this study, delivered to interns from the top six public universities in Malaysia for accounting and finance. The findings of this study show a moderate technology readiness level among the respondents. Despite respondents being optimistic about technology, they indicate feelings of discomfort towards technology. As a result, adequate focus must be given to establishing accounting expert qualifications alongside professional degrees. Their tertiary education should include more exposure to and practice technology readiness.